Intra-session reliability of knee flexion-extension muscle strength monitored using a functional electromechanical dynamometer in female soccer players - Andrades-Ramírez, Oscar; Ulloa-Díaz, David; Castillo, Bryan Alfaro; Saavedra-Ibaca, Vanessa; Muñoz-Bustos, Gustavo; Chirosa-Ríos, Luis-Javier (Frontiers in Physiology, 2025)
BackgroundThe aim of the study was to analyze the relative and absolute reliability of intra-session comparisons of three repetitions in a protocol for assessment peak muscle strength in a knee extension and flexion exercise in competitive female soccer players.MethodsThe participants in this research are professional level female soccer players. Peak muscle strength was assessed with functional electromechanical dynamometry (FEMD) for the knee muscles with the following movements: knee flexion (FLE) and extension (EXT). Each movement was assessed at a speed of 0.4 m·s-1 unilaterally, recording peak muscle strength values in the concentric phase (CON) and an eccentric phase (ECC).ResultsNull differences (ES < 0.19) were detected in the measurements of peak muscle strength of the extensors and flexors of the right and left knee in their concentric or eccentric phases. In the intra-set reliability measures, they reported acceptable absolute reliability (CV% < 9.71) and extremely high relative reliability (ICC = 0.92–0.98).ConclusionIn relation to the results of this study, it can be concluded that the FEMD presents a high relative and absolute intra-series reliability for the evaluation of muscle strength in knee extension and flexion in female soccer players. These reported antecedents may facilitate a more specific evaluation of the function of the muscles of the lower limbs.